Serial liquid biopsies for detection of treatment failure and profiling of resistance mechanisms in KLC1-ALK-rearranged lung cancer - Dietz, Steffen; Christopoulos, Petros; Gu, Lisa; Volckmar, Anna-Lena; Endris, Volker; Yuan, Zhao; Ogrodnik, Simon; Zemojtel, Tomasz; Heußel, Claus Peter; Schneider, Marc; Meister, Michael; Muley, Thomas; et al. (Cold Spring Harbor molecular case studies, 2019)
Genetic rearrangements involving the anaplastic lymphoma kinase (ALK) gene confer sensitivity to ALK tyrosine kinase inhibitors (TKIs) and superior outcome in non-small-cell lung cancer (NSCLC). However, clinical courses vary widely, and recent studies suggest that molecular profiling of ALK+ NSCLC can provide additional predictors of therapy response that could assist further individualization of patient management. As repeated tissue biopsies often pose technical difficulties and significant procedural risk, analysis of tumor constituents circulating in the blood, including ctDNA and various proteins, is increasingly recognized as an alternative method of tumor sampling (“liquid biopsy”). Here, we report the case of a KLC1-ALK-rearranged NSCLC patient responding to crizotinib treatment and demonstrate how analysis of plasma and serum biomarkers can be used to identify the ALK fusion partner and monitor therapy over time. Results of ctDNA sequencing and copy-number alteration profiling as well as serum protein concentrations at various time points during therapy reflected the current remission status and could predict the subsequent clinical course. At the time of disease progression, we identified four distinct secondary mutations in the ALK gene in ctDNA potentially causing treatment failure, accompanied by rising levels of CEA and CYFRA 21-1. Moreover, several copy-number variations were detected at the end of the treatment, including an amplification of a region on Chromosome 12 encompassing the TP53 regulator MDM2. In summary, our findings illustrate the utility of noninvasive longitudinal molecular profiling for assessing remission status, exploring mechanisms of treatment failure, predicting subsequent clinical course, and dissecting dynamics of drug-resistant clones in ALK+ lung cancer.
Gesehen am 22.04.2020